Proceedings of the 2021 Conference on Human Information Interaction and Retrieval - Scholer, Falk; Thomas, Paul; Elsweiler, David; Joho, Hideo; Kando, Noriko; Smith, Catherine (2021)
We are delighted to welcome you to the ACM SIGIR Conference on Human Information Interaction and Retrieval (CHIIR 2021), held online on March 14-19, 2021. By this sixth edition, CHIIR has established itself as a distinctively interdisciplinary event with a range of contributions at the intersection of information retrieval, human-computer interaction, and information behaviour, and we are pleased to see a variety of interesting and timely work this year. Due to the COVID-19 pandemic, we were forced to move this edition of CHIIR online. Originally, however, we intended to hold CHIIR 2021 in Canberra, Australia. We would like to acknowledge the traditional custodians of the Canberra region, the Ngunnawal people. We wish to recognise and respect their continuing culture and the contribution they make to the life of this city and this region. The conference is supported by a committed and friendly community of authors, attendees, and volunteers. Organizing and running a conference is truly a community effort, and we would like to thank those who contributed to making CHIIR '21 a success. We first thank our wonderful Program Chairs, David Elsweiler, Hideo Joho, Noriko Kando, and Catherine Smith, who spent a considerable amount of time and effort building a fantastic program for CHIIR 2021. Laurianne Sitbon and Morgan Harvey did an excellent job managing the short communications, which included short papers, demonstrations, and resource papers. Thanks to our Workshop and Tutorial chairs Henry Feild and Dana McKay, CHIIR 2021 will host three tutorials and four workshops covering a range of interesting topics. The Doctoral Consortium chairs, Katriina Byström and Gerd Berget, ensured participating students will receive world-class mentorship from leaders of the field. Matt Adcock organised our special panel session. We are grateful for the efforts of the Sponsorships Chair, Damiano Spina; the Publicity Chair, Johanne Trippas; the Proceedings Chair, Joel Mackenzie; our student volunteers; and for guidance provided by Alistair Moffat. We are also grateful for the contributions of Judy Kay and Ashlee Edwards, our keynote speakers. We thank ACM SIGIR for their generous sponsorship of CHIIR 2021, and both Google and Bloomberg for their additional support. Last, but certainly not least, we thank the many authors, senior program committee members, and program committee members, for their significant contributions to the wonderful program this year.